Murder along the Cape Fear: a North Carolina town in the twentieth century - Morgan, David T. (Mercer University Press, 2005)
A century ends, another begins -- The decade in which Fort Bragg arrived on the scene, 1911-1920 --Whiskey and murder during the roaring twenties -- Depression and murder: the 1930s -- War and murder: the 1940s -- More war, more murder: the 1950s -- Industrial strides, racial strife, Vietnam, and Jeffrey MacDonald: the 1960s -- Velma Barfield moves into the spotlight with Jeffrey MacDonald: the 1970s -- Trying to overcome the "Fayettenam" image: the 1980s -- More revitalization, more deployments, and hate crimes: the 1990s